Planetary Demons in Early Jewish Literature - Toepel, Alexander (Journal for the study of the pseudepigrapha, 2005)
Within the process of cultural exchange taking place during the Hellenistic age Babylonian and Greek astronomy and astrology were received and transformed by Jewish authors. Among these originally pagan ideas is the concept of planets as powerful and sometimes malign spiritual beings, whose rule extends over the course of history and the human body. Instances of this motif can be found in the Qumran fragments 4Q552-553 and in Testament of Reuben 2.1-3.7. On this basis the question is raised whether the tutelary angels of nations in Daniel 10.13, 20, 21 are in fact planetary deities.